Implikasi atas Penyebaran Informasi Bisnis pada Rahasia Dagang - Guntur Supriyadi (Publikasi Indonesia, 2025)
The evolution of the current economic industry shows high complexity. Industrial development needs to focus on added value. Therefore, protection of Intellectual Property Rights (IPR) is very important to protect intellectual works and trade secrets, despite the risk of fraud in competition. However, the development of trade can also threaten this confidentiality, so there needs to be legal regulations to protect trade secrets. This study focuses on examining the implications of the dissemination of business information on trade secrets. The method used is a normative legal approach, which is related to applicable laws and regulations. The results of the study show that company information is the key to competitive advantage, but is often threatened by leakage by employees or third parties. To protect trade secrets, companies need to make work agreements. However, loss of confidentiality can occur, either through employee errors or theft by insiders. Violation of trade secrets is detrimental to the economy and competitiveness of the company. In this case, company law protects trade secrets without registration, and violators can be subject to penalties.